2008
DOI: 10.1051/0004-6361:20078285
|View full text |Cite
|
Sign up to set email alerts
|

Star formation and bar instability in cosmological halos

Abstract: Context. This is the third in a series of papers presenting the first attempt to analyse the growth of the bar instability in a consistent cosmological scenario. In the previous two articles, we explored the role of the cosmology on stellar disks and the impact of the gaseous component on a disk embedded in a cosmological dark matter halo. Aims. The aim of this paper is to point out the impact of the star formation on the bar instability inside disks having different gas fractions. Methods. We performed cosmol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…Moreover, low-mass galaxies are susceptible to episodic (bursty) star formation events (Bauer et al 20013), well reproduced by our simulation. As discussed in several previous papers (Mazzei & Curir 2001;Curir et al 2008, and references therein) in DM dominated disks, as in this case (Fig. 11), the patchy and lopsided morphology of the system, showing a faint inner bar and an outer semiring, arises from the disk instability induced by the halo gravitational instability itself, which is enhanced by the interaction.…”
Section: Matching the Ngc 3447a/ngc 3447 System Propertiessupporting
confidence: 73%
“…Moreover, low-mass galaxies are susceptible to episodic (bursty) star formation events (Bauer et al 20013), well reproduced by our simulation. As discussed in several previous papers (Mazzei & Curir 2001;Curir et al 2008, and references therein) in DM dominated disks, as in this case (Fig. 11), the patchy and lopsided morphology of the system, showing a faint inner bar and an outer semiring, arises from the disk instability induced by the halo gravitational instability itself, which is enhanced by the interaction.…”
Section: Matching the Ngc 3447a/ngc 3447 System Propertiessupporting
confidence: 73%
“…Clearly the theoretical ingredients of the Bekki (2007) Lisker et al 2006a), this may be accomplished by either an enhanced disk/spheroid growth mode and/or suppression of the nuclear mass accumulation mechanism, e.g. via advective angular momentum transport, bar instabilities, and/or the presence of a central black hole (Curir et al 2008(Curir et al , 2010Foyle et al 2010;Goz et al 2015;James & Percival 2018).…”
Section: Model Predictionsmentioning
confidence: 99%
“…Curir et al (2006) built zoomed Initial Conditions (hereafter ICs) of DM halos in cosmological volumes, let them evolve with an N-body code and placed model disks inside the halos that were present at some specified redshift. That paper considered purely stellar disks, while stellar+gas disks were presented in Curir et al (2007) and the effect of star formation was considered in Curir et al (2008). In these works it was shown that halo triaxiality, at the level commonly found in simulated DM halos, triggers the formation of bars.…”
Section: Introductionmentioning
confidence: 99%